Pre-Design of Cepokolimo Tourism Village Development, Pacet District, Mojokerto Regency - Zakaria Ian Bahroni; Soebagio Soebagio; Dwi Haryanta (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Cepokolimo Village, Pacet District, Mojokerto Regency has a lot of tourism potential in the form of forestry, hills, agriculture, and natural beauty. In addition, Cepokolimo Village is located in a strategic area, namely Pacet District which is one of the areas with popular tourist destinations in East Java Province. However, this potential cannot be optimized so that it does not encourage the pace of economic growth, increase human resources, social, cultural, and welfare of the people of Cepokolimo Village. This study aims to analyze the feasibility of developing the Cepokolimo Village area to be used as a tourist destination, as well as planning the concept and drawings of tourism plans as well as calculating the required financing budget. The feasibility analysis of tourism development in this study uses the ADO-ODTWA analysis with the results of the analysis in the form of an average feasibility index of 74.09% with a feasibility level that has the potential to be developed. The initial planning for the construction was in the form of Swimming Pool Planning, Café Planning, Land planning, Fish Pond Planning, and Theater Room Planning.